2014
DOI: 10.1139/cjp-2013-0627
|View full text |Cite
|
Sign up to set email alerts
|

Impact of doped microcrystalline silicon oxide layers on crystalline silicon surface passivation

Abstract: This paper reports on a comparative study of the impact of phosphorous and boron doped microcrystalline silicon oxide (μc-SiOx:H) layers on the surface passivation of n- and p-type doped crystalline silicon float zone wafers in correlation with the material properties of the μc-SiOx:H layers. The poor surface passivation of μc-SiOx:H films deposited directly on c-Si surface might be attributed to the incorporation of doping impurities, the surface damaging by ion bombardment and (or) the low amount of hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This trend is independent of the microstructure being amorphous or nanocrystalline [51]. Accordingly, Ding et al [52] reported, for doped nc-SiO x :H layers, a similar oxygen content despite the strongly higher Fc of n-type films (above 60%) over p-type once (below 20%). This result suggests that the doping gas nature can influence the nanocrystalline evolution.…”
Section: Nanocrystalline Silicon Material: Properties and Challengesmentioning
confidence: 81%
“…This trend is independent of the microstructure being amorphous or nanocrystalline [51]. Accordingly, Ding et al [52] reported, for doped nc-SiO x :H layers, a similar oxygen content despite the strongly higher Fc of n-type films (above 60%) over p-type once (below 20%). This result suggests that the doping gas nature can influence the nanocrystalline evolution.…”
Section: Nanocrystalline Silicon Material: Properties and Challengesmentioning
confidence: 81%
“…This is due to its broad range of optical and electrical properties, which can be tuned by varying deposition parameters: i.e., absorption coefficient, refractive index, optical band gap, and p-type and n-type doping, which allow it to make selective contacts. Doping films with phosphorus (n-type) has resulted in further improved conductivities, and hydrogen atoms in the mixture have resulted in effective defect passivation [5]. Nanocrystalline silicon oxide (nc-SiOx:H) consists of crystalline silicon nanoparticles embedded in an amorphous phase composed of silicon oxide (a-SiOx:H) and a-Si:H phases [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy are the advantages as contact and/or window layer both in thin film and silicon wafer based heterojunction solar cells due to their lower (parasitic) absorption and higher conductivity. Alloying with oxygen (nc‐SiO x :H) helps to reduce parasitic absorption further and, moreover, reduces reflection of the incoming light in case of SHJ . The two‐phase character of this material permits to tune its optical and electrical properties in a wide range by varying the gas mixture, doping, and deposition conditions .…”
Section: Introductionmentioning
confidence: 99%